Gas-Kinetic BGK Scheme for Supersonic Channel Flow Simulation - Chit, Ong J.; Omar, Ashraf A.; Asrar, Waqar; Ismail, Ahmad Faris (2006)
In this paper, the gas-kinetic BGK (Bhatnagar-Gross-Krook) scheme is developed for simulating compressible inviscid supersonic channel flow. BGK scheme is an approximate Riemann solver that uses the collisional Boltzmann equation as the governing equation for flow evolutions. For efficient computations, particle distribution functions in the general solution of the BGK model are simplified and used for the flow simulations. Second-order accuracy is achieved via the reconstruction of flow variables using the MUSCL (Monotone Upstream-Centered Schemes for Conservation Laws) interpolation technique together with a multistage Runge-Kutta method. The number of grid points used for the domain is 241x131 which is generated using a structured algebraic grid generation method. The computational values compared very well to those of the analytical solution.